From Kepler to Gibson. Issue 2 (3rd April 2017) - Raja, Vicente; Biener, Zvi; Chemero, Anthony
ABSTRACT: We argue that the idea of embodiment and the strategies for carrying out embodied approaches are some of the most prevalent and interdisciplinary legacies of early modern science. The idea of embodiment is simple: to explain the behavior of bodies, we must understand them as unified wholes in their environments. Embodied approaches eschew explanations in terms of qualitative descriptions of the intrinsic properties of bodies and promote explanation in terms of the interaction between bodies. This idea can be found in Kepler's optics, Descartes' physics, and Newton's physico-mathematics. The Senses Considered as Perceptual Systems (Gibson, 1966 ) is the culmination of this centuries-long embodiment movement which can be traced back to the 17th century.